Belief in AIDS Origin Conspiracy Theory and Willingness to Participate in Biomedical Research Studies: Findings in Whites, Blacks, and Hispanics in Seven Cities Across Two Surveys - Russell, Stefanie L. (2011)
PURPOSE: The purpose of this study was to determine whether a belief in the AIDS origin conspiracy theory is related to likelihood or fear of participation in research studies. METHODS: The Tuskegee Legacy Project Questionnaire was administered via random-digit-dialed telephone interview to black, white, and Hispanic participants in 4 cities in 1999 and 2000 (n = 1,133) and in 3 cities in 2003 (n = 1,162). RESULTS: In 1999, 27.8% of blacks, 23.6% of Hispanics, and 8% of whites (P ≤ .001) reported that it was “very or somewhat likely” that AIDS is “the result of a government plan to intentionally kill a certain group of people by genocide.” In 2003, 34.1% of blacks, 21.9% of Hispanics, and 8.4% of whites (P ≤ .001) reported the same. CONCLUSIONS: Whereas blacks and Hispanics were more than 3 times more likely than whites to believe in this AIDS origin conspiracy theory, holding this belief was not associated with a decreased likelihood of participation in, or increased fear of participation in, biomedical research.